Effect of staining beverages on color stability of composite: A spectrophotometric study - Radhika Thakkar; Anuj P Maini; Sahil Mogla; Syed Shah Hussain Qadri; Praveen K Varma; Alok Dubey (Wolters Kluwer Medknow Publications, 2024)
Objective: This study used spectrophotometry to examine how staining beverages affect the color stability of three commercial composite materials (nanohybrid composite (A), bulk fill composite (B), and flowable composite (C)) over time. Materials and Methods: Composite discs were randomly divided into groups. The specimens were kept in coffee, tea, red wine, and cola for 14 days at 37°C in the dark. At baseline, 7 days, and 14 days, spectrophotometers measured color. Calculated and analyzed color differences (E). Results: Staining beverages changed the color of all composites. Composite material A had the best color stability, whereas material C stained beverages the most. Red wine and coffee discolored composites most. Discoloration increased over the 14-day immersion period. Conclusion: Composite materials with better color stability were material A. Red wine and coffee discolored composites most. When choosing restorative materials, dentists should consider composite materials' color stability for long-lasting, visually acceptable results.